2013
DOI: 10.1590/s0482-50042013000400007
|View full text |Cite
|
Sign up to set email alerts
|

Síndrome antissintetase: anti-PL-7, anti-PL-12 e anti-EJ

Abstract: ASS (anti-PL-7, PL-12 and EJ) was found to predominantly affect white women. Although the autoantibodies described in the present study are more related to pulmonary than joint involvement, our patients showed a significant percentage of both types of involvement and a high percentage of myopathy. We also observed a low mortality rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Regarding interstitial disease, Henrique et al [ 21 ], in a study carried out in Brazil, found a strong association between the presence of anti-PL7 (90%) or anti-PL12 (100%) and the development of interstitial disease. Although our patient 3 had a disease onset with the development of nonspecific interstitial pneumonitis, patient 1 had no compromising clinical or imaging findings, leading us to think that the disease may be different in the Colombian population than in others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding interstitial disease, Henrique et al [ 21 ], in a study carried out in Brazil, found a strong association between the presence of anti-PL7 (90%) or anti-PL12 (100%) and the development of interstitial disease. Although our patient 3 had a disease onset with the development of nonspecific interstitial pneumonitis, patient 1 had no compromising clinical or imaging findings, leading us to think that the disease may be different in the Colombian population than in others.…”
Section: Discussionmentioning
confidence: 99%
“…Although our patient 3 had a disease onset with the development of nonspecific interstitial pneumonitis, patient 1 had no compromising clinical or imaging findings, leading us to think that the disease may be different in the Colombian population than in others. Latin American citizens or, failing that, the myopathy panel could be a factor for an early diagnosis of the disease [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the anti-EJ type of antisynthetase syndrome primarily affects white women and has a high recurrence rate. Results of a retrospective cohort study showed that half of all patients with anti-EJ antibodies were diagnosed with classic dermatomyositis and clinically amyopathic dermatomyositis [13]. …”
Section: Discussionmentioning
confidence: 99%